Evaluation of maxillary transverse dimensions in individuals with a unilaterally impacted canine - Ibtisam A Alshalawi; Dalal M Alnahad; Husam I Ardah; Wael M Aboelmaaty; Najla S Alrejaye (Journal of Orthodontic Science, 2024)
INTRODUCTION: The aim of this study was to investigate the maxillary width within individuals with a unilaterally impacted maxillary canine and to determine any association between the impacted canine location and some canine-related variables. METHODS: A cross-sectional analytical study using a split-mouth design included 22 CBCTs of individuals with unilaterally impacted maxillary canines (a total of 44 sides). The maxillary width was measured and compared in both impacted and non-impacted sides at various levels: basal, alveolar, and dental. The following canine-related variables were analyzed and compared with impaction location: impacted canine angulation, cusp tip distance from the occlusal plane, type of impaction (vertical or horizontal), presence of root resorption, deciduous teeth, or adjacent teeth transposition. Significance was considered at P < 0.05. RESULTS: There was a significant reduction in maxillary width on the impacted side at the following levels: maxillary first premolar alveolar crest in both coronal and axial sections, dental width measured from the central fossa of maxillary first molar to the midline, and width measured from the canine cusp tip to the midline. Moreover, the distance from the palatally impacted canine cusp tip to the occlusal plane was statistically significantly lower (7.6 ± 1.5 mm) compared to buccal (10.8 ± 3.3 mm) and mid-alveolus (12.0 ± 3.9 mm) impaction, (P values = 0.02). CONCLUSIONS: There was a significant association between canine impaction and reduction in the maxillary width at least on the dental level. The palatally impacted canine cusp tip was significantly closer to the occlusal plane compared to the buccal and mid-alveolar impaction.